A study on the estimation of scattering cross section–mass bound for cold dark matter model using diffuse radio emission from galaxy clusters / Kiew Ching Yee - Kiew , Ching Yee (2018)
Galaxy clusters are the largest gravitationally bounded systems in the Universe. Approximately 80% of mass in the galaxy clusters are in the form of dark matter. Although dark matter has been proven to exist, its nature is still a mystery. The neutralino from supersymmetry theory is one of the favourite candidate for dark matter. If neutralino is the main composition of dark matter, their self-annihilation can result in synchrotron emission in galaxy clusters. On the other hand, diffuse radio emissions (e.g., radio halos, mini halos, and radio relics) are found in a small fraction of galaxy clusters. By assuming the dark matter to be composed of neutralinos, the expected synchrotron emission from the dark matter neutralinos in galaxy clusters was estimated. The constraint on the properties of neutralino was set by using the diffuse radio emission from galaxy clusters. The results showed the upper limit constraint on h_vi–m_ space with neutralino annihilates through different channels. The uncertainties on the constraint due to the dark matter density profile and cluster magnetic field were identified. The thesis also investigated the neutralino from minimial SUperGRAvity (mSUGRA) and Minimal Supersymmetric Standard Model (MSSM) models. The results showed that the neutralino can contribute partly to the diffuse radio emission, whereas the amount of which depends on the supersymmetric model adopted.